A STAT3-dependent transcriptional circuitry inhibits cytotoxic gene expression in T cells - Ciucci, Thomas (Proc Natl Acad Sci U S A, 2017)
CD8(+) T cells are preprogrammed for cytotoxic differentiation in the thymus as they acquire expression of the transcription factor Runx3. However, a subset of effector CD8(+) T cells (Tc17) produce IL-17 and fail to express cytotoxic genes. Here, we show that the transcription factors directing IL-17 production, STAT3 and RORγt, inhibit cytotoxicity despite persistent Runx3 expression. Cytotoxic gene repression did not require the transcription factor Thpok, which in CD4(+) T cells restrains Runx3 functions and cytotoxicity; and STAT3 restrained cytotoxic gene expression in CD8(+) T cells responding to viral infection in vivo. STAT3-induced RORγt represses cytotoxic genes by inhibiting the functions but not the expression of the “cytotoxic” transcription factors T-bet and Eomesodermin. Thus, the transcriptional circuitry directing IL-17 expression inhibits cytotoxic functions. However, by allowing expression of activators of the cytotoxic program, this inhibitory mechanism contributes to the instability of IL-17–producing T cells.